2019
DOI: 10.1101/828681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting glaucoma prior to its onset using deep learning

Abstract: AbstractPurposeTo assess the accuracy of deep learning models to predict glaucoma development from fundus photographs several years prior to disease onset.DesignA deep learning model for prediction of glaucomatous optic neuropathy or visual field abnormality from color fundus photographs.ParticipantsWe retrospectively i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For instance, models using CFPs have been shown capable of detecting anemia, 33 predicting cardiovascular risk factors, 34 and determining DME and glaucoma-related damage that otherwise needed optical coherence tomography (OCT) or additional tests for a diagnosis, 17,35,36 predict the progression of DR, 37 progression of age-related macular degeneration, [38][39][40] and development of glaucoma. 41 There are also several examples of algorithms for stratifying risk of DR. Estil et al used an algorithm to reduce the frequency of screening visits based on individual risk factors for DR progression. 42 Cunha-Vaz et al, 43 found that in eyes with mild non-proliferative DR, increased microaneurysm turnover rate and central macular thickness were correlated with an increased risk of progression to DME.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, models using CFPs have been shown capable of detecting anemia, 33 predicting cardiovascular risk factors, 34 and determining DME and glaucoma-related damage that otherwise needed optical coherence tomography (OCT) or additional tests for a diagnosis, 17,35,36 predict the progression of DR, 37 progression of age-related macular degeneration, [38][39][40] and development of glaucoma. 41 There are also several examples of algorithms for stratifying risk of DR. Estil et al used an algorithm to reduce the frequency of screening visits based on individual risk factors for DR progression. 42 Cunha-Vaz et al, 43 found that in eyes with mild non-proliferative DR, increased microaneurysm turnover rate and central macular thickness were correlated with an increased risk of progression to DME.…”
Section: Discussionmentioning
confidence: 99%